2000
DOI: 10.1093/jn/130.3.514
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake, Energy Balance and Serum Leptin Concentrations in Rats Fed Low-Protein Diets

Abstract: Studies examining the effects of low-protein diets on food intake and body weight have shown varied results. Many researchers have found low dietary protein to increase food intake, while others have found no effect or even a decrease. In 63 male Sprague-Dawley rats, we examined several low levels of dietary protein (2%, 5%, 8%, 10%, 15% vs. 20% casein) to determine the dose-response relationships between low dietary protein and food intake, body composition, energy balance and serum leptin concentrations. Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
110
8
9

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 32 publications
34
110
8
9
Order By: Relevance
“…Furthermore, as the chow diet contains 22% protein, a reduction of B30% of this diet will still result in a sufficient amount of protein for healthy growth (that is, comparable to a 15% protein diet). 40,41 In summary, the specific combination of a diet of saturated fat and a sugar solution, but not fat or sugar alone, results in rapid glucose intolerance and insulin unresponsiveness to a glucose load, which is not explained by levels of circulating lipids or fat mass accumulation. These data, together with previous data showing effects of a HFHS-choice diet on hypothalamic neuropeptide expression, 15 imply a role for the central nervous system in these diet-induced alterations in glucose metabolism, and in the early transition from glucose intolerance to type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the chow diet contains 22% protein, a reduction of B30% of this diet will still result in a sufficient amount of protein for healthy growth (that is, comparable to a 15% protein diet). 40,41 In summary, the specific combination of a diet of saturated fat and a sugar solution, but not fat or sugar alone, results in rapid glucose intolerance and insulin unresponsiveness to a glucose load, which is not explained by levels of circulating lipids or fat mass accumulation. These data, together with previous data showing effects of a HFHS-choice diet on hypothalamic neuropeptide expression, 15 imply a role for the central nervous system in these diet-induced alterations in glucose metabolism, and in the early transition from glucose intolerance to type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Severe nutrient deficiencies suppress dietary intake while marginal deficiencies are stimulatory. Accordingly, in rats, Du et al (2000) demonstrated increased dietary intake with moderate protein restriction (at or just below growth requirements), but decreased intake and BW in response to more severe protein restriction. This pattern of response, in addition to other factors that affect protein requirements and therefore intake (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…The most outstanding effect observed was the severe reduction in growth rate and dietary intake and as a result of protein deprivation. Previous studies have also reported inhibitory effects of low-protein diets on food intake and BW (Miura et al, 1992;Du et al, 2000;Katsumata et al, 2002), while others have reported no effect, or an increase in these parameters (VandeHaar et al, 1991;Du et al, 2000;Katsumata et al, 2002). In this connection, Forbes (2000) outlined the general relationship between the concentration of an essential nutrient in food and the rate of voluntary food intake, which is associated with concomitant changes in growth rate and other production parameters (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Os animais dos grupos controles receberam a ração normoprotéica; e os animais pertencentes aos grupos desnutridos, a ração hipoprotéica (DU; HIGGINBOTHAN;WHITE, 2000;BORELLI et al, 2007). Os animais foram submetidos aos ensaios experimentais quando o grupo desnutrido perdeu cerca de 20 % do peso inicial sendo que o peso e o consumo de ração foram avaliados a cada 48 horas .…”
Section: Indução Da Desnutriçãounclassified